TAILORING PUBLIC ADMINISTRATION REFORMS TO INDIVIDUAL NEEDS: A STUDY ON PUBLIC SERVANT PROFESSIONALIZATION - Ivanov , Petrovich Anatoliy (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study investigates the professionalisation of public servants in Ukraine in the context of public administration reforms and their individual training needs. System analysis is used as the primary method of investigation, and a content analysis of the report on the synthesis of public servants’ individual training needs for the year 2020 is conducted. The study highlights the need to improve the professionalisation process, defines the direct interconnection of public servant professionalisation with many aspects of public-service and other relations in society, and proposes possible measures to improve the efficiency of professional development for civil servants and local government officials. The findings have practical significance and can be used to improve the system of public servants’ professionalisation